Transhumanizm i posthumanizm w literaturze fantastycznej w perspektywie kliszy kulturowej i futurologicznej spekulacji = Transhumanism and posthumanism in the science-fiction literature in the perspective of the cultural cliché and futurological speculation - Trocha, Bogdan (1963- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the article the author discusses the mechanisms of the improvement of the human body that were present in the culture in the past ages. The starting points of the discussion are the ancient myths, where the figures of the heroes and hybrids appeared. They were ascribed with the important cultural functions. This situation indicates that the drive toward the improvement of human condition in its somatic dimension has existed in the culture since its beginnings. In the article, as the first ones, the mechanisms improving the body in the archaic cultures were presented, and only later the author makes the way for the analogical phenomena present in the contemporary cultures.
Keywords: posthumanizm; transhumanizm; fikcja spekulacyjna; mit; posthumanism; transhumanism; speculative fiction; myth